The Contestation of Religious Authority and Living Sunnah: The Conflict Between Ulama of Dayah and Salafis & Wahhabis in West Aceh - Noviandy Noviandy; Zulkarnain Zulkarnain; Mulyadi Mulyadi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study explores the contestation over religious authority between ulama of dayah and Salafis & Wahhabis in Meulaboh, West Aceh, highlighting the struggle for theological, cultural, and political legitimacy in the Islamic public sphere. Its primary goal is to examine how the living sunnah—the practice of sunnah intertwined with local cultural customs and the rituals of dayah—confronts the strict, text-based definition of as-sunnah promoted by Salafis and Wahhabis. Using qualitative research methods and a sociology of religion framework, this study incorporates Weberian’s authority theory and Bourdieu's habitus concept to analyze the power relations, identities, and social practices involved in the conflict. Findings reveal that this dispute is more than just an ideological or theological issue; it is a struggle for social, symbolic, and political-economic dominance, as seen in cases like Masjid Jabir al-Ka'by and local religious rituals along the west coast of Aceh. This study underscores that the contestation of the sunnah is not merely a religious debate but a social dynamic that shapes who has the authority to define authentic Islam, preserve local identity, and control the religious public sphere.